Introducing APA style for authors and researchers - Maral Yaghmaeian (فصلنامه نوآوری‌های آموزشی, 2015)
Reference to resources used in compilations and research reports validated them and supports academic honesty of author. Using a standard method of referencing in scientific literature is necessary to determine the correctness of referencing to resources. There are different referencing methods, however, due to widespread use of American Psychological Association (APA) style in social sciences, in this paper a brief description of this style is introduced. At first in-text citation and key points in creating a reference list would be disscussed and then using some examples, how to cite resource would be explained.